Use of the paca, Cuniculus paca (Rodentia: Agoutidae) in the Sierra de Tabasco State Park, Mexico - Gallina, Sonia (2012)
Cuniculus paca is widely distributed throughout the Neotropics. Known as the paca, it is the largest rodent in the Mexican tropical forests, and one of the most used as a subsistence species for its meat. Since colonial times, this species has been subject of an unreported hunting pressure. For this reason, the aim of this work was to describe the use of the paca by the inhabitants of the Sierra de Tabasco State Park (STSP) using sampling areas in a matrix of vegetation with different degrees of disturbance, and different types of land use. We included both preserved areas: owing to the presence of large continuous areas of fragmented rainforest and areas that are not preserved, with smaller rainforest fragments and more isolated. To obtain information about paca use, we interviewed 176 people (>18 years old) who live in the STSP. All those interviewed had eaten paca meat, and indicated that this species is most frequently observed in the rainforest during the dry season. Hunting and trapping were the most common ways to obtain pacas, rather than gifting or purchasing, and firearms and dogs are used to hunt them. We estimated that these interviewed group had hunted a total of 488 paca in the year prior to the study.